Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4103/0366-6999.244118
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Proximal Femoral Geometry and Risk Factors between Femoral Neck Fractures and Femoral Intertrochanteric Fractures in an Elderly Chinese Population

Abstract: Background:Few studies have investigated the differences in proximal femoral geometry and risk factors between patients with different types of hip fracture, especially in elderly Chinese. This study aimed to assess the differences in proximal femoral geometry parameters between patients with femoral neck fractures and patients with intertrochanteric fractures to provide guidance for individualized customized prosthesis and accurate reconstruction of proximal femurs in elderly Chinese patients.Methods:We retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 29 publications
(33 reference statements)
4
40
1
Order By: Relevance
“…In our study, the mean HAL of 33 patients with FNFs was 123.5 ± 14.9 mm, and the HAL of 81 patients with ITFs was 119.3 ± 12.3 mm, but there were no statistically signi cant differences. We found that the hip axis was longer in the FNF group than in the ITF group, which contrasts the results from the study by Hu et al [4].…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, the mean HAL of 33 patients with FNFs was 123.5 ± 14.9 mm, and the HAL of 81 patients with ITFs was 119.3 ± 12.3 mm, but there were no statistically signi cant differences. We found that the hip axis was longer in the FNF group than in the ITF group, which contrasts the results from the study by Hu et al [4].…”
Section: Discussioncontrasting
confidence: 99%
“…However, it is proposed in the study of Sun et al [ 14 ] that CT diagnosis conducted for patients with femoral neck stress injury in the early stage can solve image overlap, display fine details more clearly, and focus on the density of medullary cavity change, but it is still far from being ideal for the ligament injury due to trauma, and scans may be affected by partial volume effect, restricted by soft tissue resolution, misdiagnosis, and diagnosis. In view of this, it is proposed in the study of Hu et al [ 15 ] that the combination of CT and MR can be applied for patients with femoral neck stress injury in the early differential diagnosis. The multisequence and multilayer scanning of the femoral neck position by MR will find the limited hemorrhage of bone marrow cavity, fracture line, and periosteum reaction timely, show the local callus formation or cortical thickening reaction clearly, and improve the diagnostic accuracy by combining CT and clinical signs.…”
Section: Discussionmentioning
confidence: 99%
“…Internal fixation is one of the most important surgical treatments for osteoporotic fracture. There are many kinds of internal fixation materials, including Mg-Ca alloys, Zn alloy, and Ti alloys [29]. Among them, the current most clinically applied alloy is the Mg-Ca alloy.…”
Section: Introductionmentioning
confidence: 99%